Effects of NAT2 polymorphism on SASP pharmacokinetics in Chinese population - Ma, Jing-Jing; Liu, Cun-Gang; Li, Jin-Heng; Cao, Xiao-Mei; Sun, Sheng-Li; Yao, Xuan (Clinica chimica acta, 2009)
Sulfasalazine (SASP) pharmacologic actions are widely applied in clinical therapy. The role of N-Acetyltransferase 2 (NAT2) in the pharmacokinetics of SASP and its metabolites has not been clarified. We investigated the effects of genetic polymorphism of NAT2 on pharmacokinetic profiles of SASP and its two metabolites, sulfapyridine (SP) and N-acetylsufapyridine (AcSP). Eighteen subjects were recruited and divided into 3 groups by NAT2 genotype: wild type (w/w), heterozygous variant (w/m), homozygous variant (m/m). After taking 1000 mg SASP tablets, the plasma concentrations of SASP, SP and AcSP were measured with HPLC method and pharmacokinetic parameters were calculated by using the computing program 3P97. The AUC 0 – 72 and Cmax of SP in m/m subjects were significantly higher than those in w/m and w/w subjects, with the values of 172.57 ± 49.42, 103.38 ± 39.85, 71.37 ± 17.52 mg h/l, and 9.65 ± 2.34, 6.10 ± 1.79, 4.55 ± 1.38 mg/l, respectively. In contrast, the AUC 0 – 72 of AcSP was significantly lower in m/m subjects. The Cmax of AcSP in w/w, w/m and m/m subjects was 12.67 ± 3.32, 9.07 ± 2.29 and 4.22 ± 0.93 mg/l, respectively, with significant differences among groups. However, there was no significant difference in any pharmacokinetic parameter of SASP among groups. Different NAT2 genotypes, leading to functional heterogeneity of NAT2, may affect pharmacokinetics of SP and AcSP. Therefore, genotyping NAT2 gene before administration would be important in SASP therapy.